ANALISIS PENGARUH SUKUK TERHADAP PEMBIAYAAN PEMBANGUNAN INFRASTRUKTUR DI INDOENSIA TAHUN 2014 – 2018 - Arif Pangestu Abitaha; Aris Soelistyo (Jurnal Ilmu Ekonomi, 2021)
Infrastructure is one of the important values to support economic growth and development in a country. Inadequate infrastructure will hinder the country's progress and competition compared to other countries. One of the breakthrough sources of financing funds is the use of sharia bonds or what is known as Sukuk. Infrastructure financing through the issuance of Sukuk has been implemented since 2010 with the Project-Based Sukuk (PBS) series. The Indonesian Hajj Fund Sukuk (SDHI), Retail Sukuk (SR), and Project Base Sukuk (PBS) are three of the parts contained in the Sukuk. The purpose of this research is to provide an overview of the development of SDHI, SR, and PBS in financing infrastructure development in Indonesia. By looking at the level of the problem of public goods or can be called public facilities owned by the State.